Theoretical properties of two estimators in partially linear single-index measurement error models - Hua Liang; Naisyin Wang (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
Considering partially linear single-index errors-in-variables model which can be described as Y = n(X T a) + ZT ßo + e when the Z' s are measured with additive errors. The general estimators established in literature are biased when ignoring the measurement errors. We proposed two estimators in this setting. Their theoretical properties were derived and compared.
urn:nbn:de:kobv:11-10046906
Keywords: 330